Factors Affecting the Accuracy of Providing an Audit Opinion - Melan Sinaga; Linawati Linawati (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
The study aimed to identify factors affect the accuracy of the audit opinion in partial and together. The method used in this study is multiple linear regression with a accidental sampling method with a sample of 68 respondents. The variables used in this research was the accuracy of the audit opinion as, dependent variable of audit evidence, experience an auditor, audit situation as the independent variable. The data used in this study was the primary data, which are questionnaires distributed at 17 public accounting firms located in South Jakarta. The results showed that partially the competence of the auditor had a positive and significant effect, audit evidence had a positive and significant effect, the auditor’s experience had a positive and significant effect, audits of the situation had no effect on accuracy of the provision of an audit opinion